International Tourism Demand in Bangladesh: An ARDL Bounds Test Approach - Murshed, Muntasir (Journal of Tourism Management Research, 2019)
Tourism can somewhat be compared to the Cinderella industry, much because of its development being unattended despite having immense potentials in generating development within an economy. This paper aims to fill the gap in the literature by modeling tourist demand in Bangladesh as a function of its real fundamentals using time series data over the period 1980 to 2017. Augmented Dickey-Fuller (ADF) unit root tests along with the Autoregressive Distributed Lag (ARDL) bounds testing approach to cointegration and causality analyses are considered. The results reveal that the relative cost of living in Bangladesh and travel costs negatively affect international tourism demand while the relative cost of living in India, national income and exchange rate are found to be positively associated to tourism demand in Bangladesh. Moreover, long run causalities stemming from all the explanatory variables to tourism demand are also established in light of the statistical evidence found. Thus, it is pertinent for the government to escalate tourism development in Bangladesh which can also play a pivotal role in the diversification of the nation's export basket.